Minimally Invasive L5–S1 Anterior TLIF Cage Placement in Lateral ALIF Exposure as a Bailout Option for Low Iliocaval Junctions: Report of Four Cases - Kim, Timothy Y.; Pham, Martin H. (Asian Journal of Neurosurgery, 2025)
The aim of this study was to demonstrate that anteriorly placed transforaminal lumbar interbody fusion (TLIF) footprint bullet cage is a safe and effective bailout option if difficult left common iliac vein (LCIV) anatomy is unexpectedly encountered during the L5–S1 lateral anterior lumbar interbody fusion (L-ALIF). This retrospective case series includes four patients who received anteriorly placed TLIF cages at L5–S1 during L-ALIF surgery. Demographics, complications, and clinical/radiographic results were collected. The analysis included four female patients with a mean age of 59.0 years and mean body mass index (BMI) of 23.9. Three patients had degenerative conditions and one patient had a deformity. All the patients had an LCIV obstructing the center of the L5–S1 disk space, and titanium TLIF bullet cages were placed and secured with washers and screws. The L5–S1 segmental lordosis increased by 8.3 ± 6.1 degrees with a final mean lordosis of 23.5 ± 8.4 degrees; the L5–S1 intradiskal angle increased by 12.0 ± 7.0 degrees with a final mean disk angle of 18.8 ± 7.0 degrees; the posterior disk height increased by 4.4 ± 2.7 mm with a final mean disk height of 8.0 ± 2.1 mm. The mean numerical rating scale (NRS) for back pain improved by 5.3 ± 2.5 and the mean NRS leg pain improved by 7.7 ± 2.5 over a mean follow-up of 14 months (range: 6–20). There have been no perioperative complications or implant failure to date. If challenging vascular anatomy is encountered during L-ALIF exposure that prevents ALIF footprint cage placement, proceeding with smaller TLIF bullet cage placement anteriorly rather than abandoning the surgical approach is a safe and effective option.
Keywords: L5–S1 spine; degenerative spondylosis; lateral ALIF; TLIF; single position surgery